2011
DOI: 10.1080/18811248.2011.9711815
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Crack Initiation in Proton-Irradiated Austenitic Stainless Steel

Abstract: The effect of irradiation on slip band formation and growth and microcrack initiation behavior under low cycle fatigue in SUS316L austenitic stainless steel was investigated using accelerator-based proton irradiation and a low cycle fatigue test at room temperature in air. The mean space of the slip line in proton-irradiated specimens was 25-40% wider than that in unirradiated specimens under the same number of cycles, possibly due to localized deformation by proton irradiation. The microcrack initiation life … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Dislocation channels are characterized by their width (~0.1 µm), spacing (generally 1-3 µm), and the amount of shear strain in the channel [11], [12]. The amount of shear strain in the dislocation channels is difficult to analyze experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…Dislocation channels are characterized by their width (~0.1 µm), spacing (generally 1-3 µm), and the amount of shear strain in the channel [11], [12]. The amount of shear strain in the dislocation channels is difficult to analyze experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…A distinguished feature observed in irradiated materials is the formation of defect-free channels (or say dislocation channels) after plastic deformation [118] as illustrated in Figure 8. The dominant characters of defect-free channels involve the channel width (around 0.1 µm), inter-channel spacing (about 1-3 µm) and the amount of accumulated shear strain in channels [119,120]. Through measuring the step height on the surface of irradiated samples and the offset caused by the channel-grain boundary intersection, the amount of shear strain in channels is estimated to be about two orders of magnitude higher than that of bulk materials without irradiation effect [121].…”
Section: Formation Of Defect-free Channelsmentioning
confidence: 99%
“…Fenici and Suolang found that proton‐irradiated austenitic steel was more resistant to crack initiation and had a reduced crack growth rate compared with unirradiated controls when using load‐controlled testing. Nogami et al found the opposite behaviour in low‐cycle, strain‐controlled fatigue testing where proton irradiation reduced the time for crack initiation. Murase et al found an increase in fatigue life due to proton irradiation, as did Shulov and Nochovnaya for metals subject to heavy ion irradiation.…”
Section: Introductionmentioning
confidence: 99%